Pemanfaatan Digitalisasi untuk Meningkatkan Kompetensi SDM dalam Pengelolaan Administrasi Perpajakan pada UMKM - Nurul Maharani; Vaudi Windi Aulia; Khoirul Umam; Moh Rifky Syahbani; Junaidi Efendi (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the use of digitalization in improving human resource (HR) competency in managing UMKM tax administration. The research method used is a literature study utilizing secondary data obtained from books, journal articles, and various relevant scientific publications for the period 2021–2026. Data collection was conducted through a literature search on Google Scholar, ScienceDirect, and Mendeley with keywords related to tax digitalization, HR competency, and UMKM. The results show that tax digitalization through services such as e-filing, e-billing, and Coretax can increase the effectiveness and efficiency of UMKM tax administration. The use of digital technology helps business actors in the process of recording, reporting, paying, and storing tax documents more quickly, easily, and structured. In addition, tax digitalization also plays a role in improving HR competency, digital literacy, taxpayer compliance, and tax administration capabilities of UMKM actors. However, the implementation of tax digitalization still faces obstacles such as low digital literacy, limited technological capabilities, lack of training, and limited digital infrastructure. Therefore, support in the form of training, education, mentoring, and the provision of adequate technological facilities is needed to ensure optimal and sustainable implementation of tax digitalization in UMKM.